2003
DOI: 10.1021/bp020128f
|View full text |Cite
|
Sign up to set email alerts
|

Containment of Biogenic Sulfide Production in Continuous Up‐Flow Packed‐Bed Bioreactors with Nitrate or Nitrite

Abstract: Produced water from the Coleville oil field in Saskatchewan, Canada was used to inoculate continuous up-flow packed-bed bioreactors. When 7.8 mM sulfate and 25 mM lactate were present in the in-flowing medium, H(2)S production (souring) by sulfate-reducing bacteria (SRB) was prevented by addition of 17.5 mM nitrate or 20 mM nitrite. Changing the sulfate or lactate concentration of the in-flowing medium indicated that the concentrations of nitrate or nitrite required for containment of souring decreased proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 88 publications
3
97
1
Order By: Relevance
“…This was shown by Hubert et al (16) with a bioreactor injected with 25, 12.5, or 6.25 mM lactate and 7.8, 4.7, or 3.0 mM sulfate. Because SRB were a prominent component in all bioreactor communities that were analyzed (16), it was concluded that souring control was due primarily to NR-SOB activity, as in Fig. 1A.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…This was shown by Hubert et al (16) with a bioreactor injected with 25, 12.5, or 6.25 mM lactate and 7.8, 4.7, or 3.0 mM sulfate. Because SRB were a prominent component in all bioreactor communities that were analyzed (16), it was concluded that souring control was due primarily to NR-SOB activity, as in Fig. 1A.…”
mentioning
confidence: 60%
“…All cultures originated from the water produced from the Coleville oil field located near Kindersley, Saskatchewan, in western Canada. The water produced from the oil field sampled in August 2000 was used to inoculate bioreactors in previous studies (15,16) from which most strains described here were isolated. A sample of the water produced obtained in April 2002 was used to inoculate the bioreactor in the present study and was also plated directly for further strain isolations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of souring and its control with nitrate or nitrite have mostly used VFA or lactate as the electron donor for nitrate and sulfate reduction (15,19,21,33,34,45,46). Only Myhr et al (18) also used an oil-flooded bioreactor.…”
Section: Discussionmentioning
confidence: 99%
“…Souring of oil fields is unwanted and can be prevented or reversed by the injection of nitrate, stimulating heterotrophic nitrate-reducing bacteria (hNRB) and sulfide-oxidizing nitrate-reducing bacteria (6,7,(15)(16)(17)(18)(19)(20)(21). Both NRB activities produce nitrite as an intermediate, inhibiting dissimilatory sulfite reductase Dsr, the highly conserved enzyme that produces the sulfide (22)(23)(24).…”
mentioning
confidence: 99%